Etika Pemanfaatan Artificial Intelligence dalam Pendidikan: Mendidik Generasi yang Bertanggung Jawab terhadap Teknologi - Hidayati, Beti Malia Rahma; Sari, Ika Novita; Sugianto, Sugianto; Permatasari, Futika (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2024)
Artificial Intelligence (AI) is one of the technological inventions that attracts attention because it has the potential to revolutionize the world of education. The rapid advancement of technology has become a fundamental aspect and important instrument in managing human resource needs and maintaining social values. Digital ethics education is important to equip people with the knowledge and skills needed as a foundation for safe and responsible use of digital technology. This research uses a library research method with a qualitative approach. Data collection in this research is done by collecting various kinds of studies and literature in the form of scientific journals. This research will describe the context of AI ethics education, analyze the framework of AI ethics education and its evaluation of challenges and solutions in the implementation of AI ethics education.